The Living Qur’an in the Mandi Safar Tradition: Internalizing Qur’anic Values in Air Hitam Laut, Jambi - Rafika Dhiya Alfadhilah; Bahriyadi (Jurnal test, 2026)
Over time a dialectic has emerged between tradition and a purer understanding of religion. Some people now view the mandi safar tradition not as a fate-determining ritual (avoiding idolatry), but rather as an effort to preserve customs (culture) and a means to strengthen bonds of brotherhood among residents. This article aims to examine the internalization of the Qur’an within the cultural ritual of mandi safar and to explore its religious and cultural meanings among the community of Air Hitam Laut Village, Sadu Subdistrict, East Tanjung Jabung Regency, Jambi Province. The article employs a qualitative method with a descriptive-interpretative approach within the Living Qur’an perspective. Data were collected through field observations, in-depth interviews with religious leaders, customary figures, and community members, as well as documentation studies. The findings indicate that the mandi safar tradition represents an integration of Qur’anic values and local tradition, symbolically manifested through the use of seven salamun verses (QS. Yasin: 58, QS. As-Saffat: 79, QS. As-Saffat: 109, QS. As-Saffat: 120, QS. As-Saffat: 130, QS. Az-Zumar: 73, QS. Al-Qadr: 5) as a medium of worship, supplication for protection (repelling calamity), and social cohesion. Beyond its religious significance, the ritual also serves cultural and economic functions, reflecting the dynamic and contextual character of Islamic religiosity in Indonesia.